USM SETS UP IDEA BANK, STRATEGIC THINKING REPOSITORY - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, 26 October 2015 – Universiti Sains Malaysia (USM) has set up the USM Idea Bank to store strategic ideas contributed by its community, and to ensure such additional inputs would continue to spur the excellence in the governance of the university.